Cine 100 años de filosofía. Una introducción a la fisolofía a través del análisis de películas - CABRERA, Julio (GEDISA, 1999)
CONTENIDO : AUTORES PLATON; BACON; LOCKE, JOHN; HUME, DAVID; KANT; MORE; ARISTOTELES; HEGEL; MARX, KARL; NIETZSCHE; HEIDEGGER; SARTRE, J.P.; WITTGENSTEIN